2021
DOI: 10.1038/s41539-021-00087-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of language on performance: do gendered languages fail women in maths?

Abstract: Research suggests that gendered languages are associated with gender inequality. However, as languages are embedded in cultures, evidence for causal effects are harder to provide. We contribute to this ongoing debate by exploring the relationship between gendered languages and the gender gap in mathematics achievements. We provide evidence for causality by exploiting the prominent (but not exclusive) practice in gendered languages of using masculine generics to address women. In an experiment on a large repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…This is the first study, as far as we are aware, to provide evidence suggesting that masculine generics in the second person are biased in favour of male addressees during language processing and are not immediately perceived as gender-unspecific. The current findings thus add to the results of Kricheli-Katz and Regev ( 2021 ) who found that the use of Hebrew gender marking that mismatches addressee gender can negatively affect test performance. The results also suggest that the initial processing disadvantage that women experience when addressed with a masculine generic verb may be as strong as the effect of men being addressed through a verb with feminine gender marking.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This is the first study, as far as we are aware, to provide evidence suggesting that masculine generics in the second person are biased in favour of male addressees during language processing and are not immediately perceived as gender-unspecific. The current findings thus add to the results of Kricheli-Katz and Regev ( 2021 ) who found that the use of Hebrew gender marking that mismatches addressee gender can negatively affect test performance. The results also suggest that the initial processing disadvantage that women experience when addressed with a masculine generic verb may be as strong as the effect of men being addressed through a verb with feminine gender marking.…”
Section: Discussionsupporting
confidence: 84%
“…As far as we know, the topic of second person masculine generics was only addressed in one study (Kricheli-Katz & Regev, 2021 ) on Hebrew—a language that marks gender on verbs and where the masculine gender can also be used generically. They found that both men and women performed worse on a math test when the questions addressed them using gender marking that mismatched their own gender.…”
Section: Second Person Masculine Genericsmentioning
confidence: 99%
“…Research suggests that gendered languages like French are associated with gender inequality compared with a genderless language such as English. 26 Although we assumed gender equity may be influenced by academic language heritage (French versus English), we did not find any differences in gender equity trends based on language. While our intention was to compare Francophone and Anglophone countries, Nigeria the only Anglophone country in West Africa, demonstrated a gender representation pattern typical of the Francophone countries in West Africa.…”
Section: Discussionmentioning
confidence: 52%
“…A citation analysis suggests that Danaher and Crandall's interpretation is the more widely accepted: Scopus reports that Danaher and Crandall's [9] reanalysis has received more citations than Stricker and Ward's [10] original report (as of 21st May 2021). Furthermore, in the education literature, Danaher and Crandall's [9] interpretation is often cited without mention of Stricker and Ward [e.g., [14][15][16] and, when both authors are cited, the fact that Stricker and Ward disagreed with Danaher and Crandall is not always highlighted [e.g. , 17].…”
Section: Stereotype Threat In Real World Contextsmentioning
confidence: 99%
“…In sum, we believe that Stricker and Ward's [7] study merits replication. It is an influential study about a topic of societal importance which is often cited in policy debates and the education literature [e.g., [14][15][16][17]21]; the wider literature has cast a degree of doubt about the reliability of the theoretical mechanism proposed to underly the effect; and the dispute between Stricker and Ward [7,10] and Danaher and Crandall [9] about how to legitimately interpret the study's findings, means that if the observed effect were a false positive, it is unlikely to be due to publication bias or questionable research practices.…”
Section: Stereotype Threat In Real World Contextsmentioning
confidence: 99%